Pengembangan Media Pembelajaran Menyimak Berbasis Google Form dengan Add On Form Presenter + Timer pada Mahasiswa Universitas Khairun - Roni Kurniawan; Adityarini Kusumaningtyas (ALFABETA: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2025)
This study aims to create an easy-to-use Google Form-based listening learning tool, enhanced with the Form Presenter and Timer Add-Ons, to address the lack of language lab facilities at the Indonesian Language and Literature Education Program at Khairun University. We used a Research and Development (R&D) approach with the 4D model (Define, Design, Develop, Disseminate). The process started with a needs analysis, followed by designing the content and format, expert validation, and limited and field testing. Data was collected through expert reviews, student feedback surveys, and pre- and post-tests. The results showed the tool is highly suitable, with a 95.5% approval from content experts and 92.25% from media experts. Effectiveness tests revealed a significant improvement in student learning outcomes, with an N-gain score of 0.7, considered high. The tool was also rated practical, scoring 87% for usability. It allows students to access listening materials and questions independently on their devices, without relying on a language lab. Overall, this learning tool is effective, reliable, and practical for teaching listening courses in higher education, with strong potential to boost student performance.